When people come last - Abd Razak, Dzulkifli (2009)
WHILE the world is preoccupied with the potential pandemic caused by the influenza A, most are oblivious to the global epidemic that is prevalent in our midst: the epidemic of tobacco. Today is World No Tobacco Day, a day that serves to remind us that the war against smoking and the use of tobacco is far from over. In fact, for developing countries like Malaysia, the fight is still raging as an uphill battle with no clear winning strategy in sight.